Exploring Chinese house prices affordability in the context of confucian culture - Fang Liu; Chen Liang (PLoS ONE, 2025)
Considering the notable influence of traditional Confucian culture on China’s housing market, this study introduces an innovative index to quantify the magnitude of the real estate bubble within China, employing a familial generational iterative model. Utilizing rent-buy policy as a conceptual framework, our research constructs a difference-in-differences model to investigate the impact of macroeconomic policies on the housing bubble phenomenon. Empirical observations from 2022 reveal pronounced bubble dynamics in first and second-tier cities, while housing prices in third and fourth-tier cities, alongside select fifth-tier cities, exhibit a declining trend. On a national scale, apart from minor affordability observed during 2005–2007, no significant affordability was identified in other years, with the housing price bubble index demonstrating a downward trajectory from 2020 to 2022. Furthermore, the implementation of the rent-buy policy that equality the rights of renter and owner has directly influenced the housing market, notably mitigating the overall escalation of housing prices. Additional analysis indicates that the rent-and-buy policy has been more successful in curbing price hikes in newly constructed and smaller-sized housing units compared to second-hand and larger-scale properties.